Measuring the Sustainability of Online Researcher Functional Position Formation Training using the CIPP (Context, Input, Process, and Product) Model Evaluation Approach - heru sukoco, sutrisno; Indah Kurniadewi, Yogtavia (Monas: Jurnal Inovasi Aparatur, 2023)
Researcher Functional Position Formation Training (PPJFP) is a prerequisite that must be fulfilled by prospective expert researchers. The discourse on implementing PPJFP training online was planned before the occurrence of the COVID-19 pandemic; however, the widespread impact of the pandemic necessitated an immediate transformation of the training from offline to online. The aim of this research is to measure the success of the fully online PPJFP training, requiring an evaluation for decision-making on whether to continue, improve, or possibly discontinue the program. The CIPP model (Context, Input, Process, and Product) is deemed adequate for evaluating the implementation of fully online PPJFP. The study involved 144 participants in the PPJFP training program in 2021, utilizing a quantitative-descriptive method as the research approach. Evaluation results indicate that the fully online implementation of PPJFP is considered to meet participants' expectations and needs. This is evident from the majority of participants rating the effectiveness of learning, instructor and mentor competence, participant motivation, and academic benefits as highly suitable. The curriculum, the competence of involved instructors and mentors, and the provided learning infrastructure are perceived to meet participants' expectations. Both asynchronous and synchronous learning methods are considered highly suitable and effective. One indicator of the success of this training is the increased motivation and interest in becoming researchers. 63.89% of participants express greater confidence and readiness to become researchers, 31.25% feel confident and ready, and 4.86% feel sufficiently confident. Based on the evaluation results, it can be concluded that conducting PPJFP training online is feasible for the coming years. The findings of this research are expected to provide insights for training organizers to enhance the quality of training programs and their implementation in the subsequent years.